O-026 Initial clinical experience with the web intrasaccular flow-diverter device for endovascular treatment of intracranial aneurysms. (12th July 2011) - Lubicz, B; Mine, B; Collignon, L; De Witte, O; Brisbois, D
Abstract : Background and Purpose: Flow diversion is a new approach for the endovascular treatment (EVT) of intracranial aneurysms (IA). The woven endobridge aneurysm embolization device (WEB) is the first intrasaccular flow-diverter device dedicated to IA treatment. We report our preliminary experience with this device. Methods: This report is part of an ongoing prospective study that was approved by the authors ethical committees. This prospective multicentric study was approved by our ethical committees. Five patients with 5 wide-necked, unruptured, and terminal-type aneurysms were included and treated by WEB placement alone. There were four women and one man with a mean age of 47 years old. Aneurysms were located on the middle cerebral artery bifurcation (n=2), on the basilar tip, on the vertebral artery, and on the carotid-ophtalmic artery. Technical issues, immediate findings, clinical and imaging follow-up at 3 months were assessed. Results: EVT was successfully performed in all but one patient who presented with a tortuous carotid siphon. In this patient, the WEB could not be delivered because of high frictions within the delivery catheter. In four patients, the WEB could be placed within the aneurysm achieving immediate occlusion with a slight neck remnant in 2 cases and major flow reduction in 2 cases. In one of these latter two patients, imaging follow-up at 3 months (magnetic resonance and conventional angiographies) was obtained showing satisfying occlusion with a neck remnant. There was no morbidity and mortality related to the procedure. However, in one patient with a middle cerebral artery aneurysm, slowing of a bifurcation branch was observed without any clinical significance. Conclusions: Intrasaccular flow-diversion is an effective new therapeutic approach for EVT of IA.